Population expansion, clonal growth, and specific differentiation patterns in primary cultures of hepatocytes induced by HGF/SF, EGF and TGF alpha in a chemically defined (HGM) medium (The Rockefeller University Press, 1996)
Mature adult parenchymal hepatocytes, typically of restricted capacity to proliferate in culture, can now enter into clonal growth under the influence of hepatocyte growth factor (scatter factor) (HGF/SF), epidermal growth factor (EGF), and transforming growth factor alpha (TGFalpha) in the presence of a new chemically defined medium (HGM). The expanding populations of hepatocytes lose expression of hepatocyte specific genes (albumin, cytochrome P450 IIB1), acquire expression of markers expressed by bile duct epithelium (cytokeratin 19), produce TGFalpha and acidic FGF and assume a very simplified morphologic phenotype by electron microscopy. A major change associated with this transition is the decrease in ratio between transcription factors C/EBPalpha and C/EBPbeta, as well as the emergence in the proliferating hepatocytes of transcription factors AP1, NFkappaB. The liver associated transcription factors HNFI, HNF3, and HNF4 are preserved throughout this process. After population expansion and clonal growth, the proliferating hepatocytes can return to mature hepatocyte phenotype in the presence of EHS gel (Matrigel). This includes complete restoration of electron microscopic structure and albumin expression. The hepatocyte cultures however can instead be induced to form acinar/ductular structures akin to bile ductules (in the presence of HGF/SF and type I collagen). These transformations affect the entire population of the hepatocytes and occur even when DNA synthesis is inhibited. Similar acinar/ductular structures are seen in embryonic liver when HGF/SF and its receptor are expressed at high levels. These findings strongly support the hypothesis that mature hepatocytes can function as or be a source of bipotential facultative hepatic stem cells (hepatoblasts). These studies also provide evidence for the growth factor and matrix signals that govern these complex phenotypic transitions of facultative stem cells which are crucial for recovery from acute and chronic liver injury.